Biological Insights of Fluoroaryl-2,2′-Bichalcophene Compounds on Multi-Drug Resistant Staphylococcus aureus - Elmogy, Sally (Molecules, 2020)
Resistance of bacteria to multiple antibiotics is a significant health problem; hence, to continually respond to this challenge, different antibacterial agents must be constantly discovered. In this work, fluoroaryl-2,2′-bichalcophene derivatives were chemically synthesized and their biological activities were evaluated against Staphylococcus aureus (S. aureus). The impact of the investigated bichalcophene derivatives was studied on the ultrastructural level via scanning electron microscopy (SEM), molecular level via sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) method and on the biofilm inhibition via the electrochemical biosensors. Arylbichalcophenes’ antibacterial activity against S. aureus was affected by the presence and location of fluorine atoms. The fluorobithiophene derivative MA-1156 displayed the best minimum inhibitory concentration (MIC) value of 16 µM among the tested fluoroarylbichalcophenes. Over a period of seven days, S. aureus did not develop any resistance against the tested fluoroarylbichalcophenes at higher concentrations. The impact of fluoroarylbichalcophenes was strong on S. aureus protein pattern showing high degrees of polymorphism. SEM micrographs of S. aureus cells treated with fluoroarylbichalcophenes displayed smaller cell-sizes, fewer numbers, arranged in a linear form and some of them were damaged when compared to the untreated cells. The bioelectrochemical measurements demonstrated the strong sensitivity of S. aureus cells to the tested fluoroarylbichalcophenes and an antibiofilm agent. Eventually, these fluoroarylbichalcophene compounds especially the MA-1156 could be recommended as effective antibacterial agents.